(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this study is to determine and analyze the legal standing of whistleblowers in exposing bribery crimes and legal protection for whistleblowers in exposing bribery crimes. This study is a normative legal study, by examining legal rules such as laws, regulations or literature in order to obtain materials in the form of concepts, theories, principles or legal regulations. The sources of legal materials used in this study include primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials in this study was carried out by means of library research, and analyzing data with a predetermined approach. The results of this study show that the position of Whistleblowers is very important in revealing criminal cases, because Whistleblowers are people who work at the place where the crime occurred, so that information can be processed to find out the truth by the authorities, can immediately take action to be further processed in accordance with applicable law. And the legal protection given to Whistleblowers in Law Number 31 of 2014 has not been able to protect Whistleblowers optimally. This is because the Law only provides protection for witnesses, victims, and reporters. The Law even provides different protection for witnesses and victims when compared to protection for reporters. There should be a socialization process that continues to encourage this, so that it can be implemented by government institutions, private companies and public institutions. and it is better to formulate a regulation that can provide legal protection for Whistleblowers. Or at least it can be included in the Criminal Procedure Code Bill. Abstrak : Tujuan penelitian ini untuk mengetahui dan menganalisis legal standing whistleblower (kedudukan hukum saksi pelaku) dalam mengungkap tindak pidana suap dan perlindungan hukum terhadap whistleblower dalam mengungkap tindak pidana suap.Penelitian ini adalah penelitian hukum normatif, dengan mengkaji aturan hukum seperti Undang-undang, peraturan-peraturan ataupun literatur guna untuk mendapatkan bahan berupa konsep, teori, asas ataupun peraturan hukum. Adapun sumber bahan hukum yang digunakan dalam penelitian ini meliputi bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Adapun teknik pengumpulan bahan hukum dalam penelitian ini dilakukan dengan cara penelitian kepustakaan (library reseacrch), serta menganalisis data dengan pendekatan yang telah ditetapkan. Hasil penelitian ini kedudukan Whistleblower sangatlah penting dalam mengungkap kasus-kasus pidana, karena Whistleblower merupakan orang yang bekerja di tempat terjadinya tindak pidana tersebut, sehingga informasi dapat diproses untuk mengetahui kebenarannya oleh aparat yang berwenang, dapat segera mengambil tindakan untuk selanjutnya di proses sesuai dengan hukum yang berlaku. Dan perlindungan hukum yang diberikan kepada Whistleblower dalam Undang-Undang Nomor 31 Tahun 2014 belum dapat melindungi Whistleblower secara maksimal. Hal ini disebabkan karena Undang-Undang tersebut hanya memberikan perlindungan sebatas terhadap saksi, korban, dan pelapor. Undang-Undang tersebut bahkan memberikan perlindungan yang berbeda bagi saksi dan korban jika dibandingkan dengan perlindungan bagi pelapor. Seharusnya ada proses sosialisasi yang terus mendorong hal tersebut, agar dapat diterapkan baik oleh Lembaga pemerintahan ,Perusahaan swasta dan institusi publik. dan sebaiknya dirumuskan suatu peraturan perundang undangan yang dapat memberikan perlindungan hukum bagi Whistleblower. Atau paling tidak dapat dimasukkan dalam RUU KUHAP.